Time-Domain Solution for Corner Diffraction of UWB Signals by Flat Plate Structures with the Higher Order Diffraction Included. Issue 5 (3rd September 2018) - Bansal, Bajrang; Soni, Sanjay; Jaiswal, Rahul Kumar; Kumar, Vinod
ABSTRACT: In this paper, a new time-domain (TD) solution is proposed for corner diffraction by finite-edge flat plate structures. First, TD solution is considered for corner amplitude diffraction by edges of a flat plate, and then for corner slope diffraction (CSD) which takes into account the finiteness of the plate edges. To show the significance of CSD, results have been shown for diffraction of ultra-wideband signals by edges of a horn antenna which is a structure made by interconnected flat plates. The comparison between the TD solution and the numerical inverse fast Fourier transform of the corresponding frequency-domain solution validates the proposed solution. Finally, the computation times of both methods have been compared.